The Material Culture of German Texans - Hafertepe, Kenneth, 1955- (Book collections on Project MUSE., 2016)
German immigrants of the nineteenth century left a distinctive mark on the lifestyles and vernacular architecture of Texas. In this first comprehensive survey of the art and artifacts of German Texans, Kenneth Hafertepe explores how their material culture was influenced by their European roots, how it was adapted to everyday life in Texas, and how it changed over time-at different rates in different communities. The Material Culture of German Texans is about the struggle to become American while maintaining a distinctive cultural identity drawn from German heritage. Including materials from ru.